2021
DOI: 10.1111/jocd.14140
|View full text |Cite
|
Sign up to set email alerts
|

Oral tranexamic acid, hydroquinone 4% and low‐fluence 1064 nm Q‐switched Nd:YAG laser for mixed melasma: Clinical and dermoscopic evaluation

Abstract: Background: Tranexamic acid (TA) can prevent melanocyte activation by various stimuli. Combining TA with either hydroquinone 4% or Q-switched Nd:YAG laser may be associated with greater improvement of melasma. Objectives:We aimed to evaluate the efficacy and safety of oral TA alone and combined with either topical hydroquinone 4% or low-fluence 1064 nm Q-switched Nd:YAG laser in treatment of mixed melasma.Patients & Methods: Patients were randomly divided into three groups of 20 patients each. Group A were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…The present study revealed that the therapeutic effect of oTA combined with routine topical agents is superior to that of oTA alone, topical TA, iTA, MNsTA in the long term. This result is consistent with a previous study in Elkamshoushi's opinion 37 that combining 4%HQ with oTA achieves an earlier and better cosmetic improvement than oTA alone. Natalia et al 71 combination of oTA with topical therapy utilizing HQ and retinoid products is recommended as a first-line treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study revealed that the therapeutic effect of oTA combined with routine topical agents is superior to that of oTA alone, topical TA, iTA, MNsTA in the long term. This result is consistent with a previous study in Elkamshoushi's opinion 37 that combining 4%HQ with oTA achieves an earlier and better cosmetic improvement than oTA alone. Natalia et al 71 combination of oTA with topical therapy utilizing HQ and retinoid products is recommended as a first-line treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Elkamshoushi et al 37 suggested that the reason might be that TA treatment should be long-term and needs long-term maintenance. Once TA is stopped for several months, patients who take TA orally or in combination with conventional external drugs have a certain degree of recurrence and an elevated MASI, which is also consistent with the results reported by Ebrahim et al 33 In conclusion, we figured that oTA + RTA is the best mode of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Then, by screening the titles and abstracts, we further eliminated 793 studies. Ultimately, 39 randomized clinical trials 12,18–55 were included in the network meta‐analysis. The flowchart of screening and selection is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Since there is no cell death and skin heating is kept to a minimum, the risk of melasma exacerbation is much lower. This technique achieved the best results and the lowest risk of recurrence when it is combined with other agents such as topical HQ [199,200], triple combination cream [201], azelaic acid [202], chemical peels, e.g., Jessner's formula [203,204], GA [205,206] and systemic treatment with TA [199,[207][208][209][210], as well as other treatment procedures, such as microneedling with ascorbic acid [211], microneedle radiofrequency (RF) [212], microdermabrasion [213], pulsed-dye laser [214], and IPL [188,215,216]. In each of these cases, combination therapy was more effective than the laser toning procedure alone [197,217].…”
Section: Laser Therapymentioning
confidence: 99%